2010
DOI: 10.3354/dao02240
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of probiotic- and triherbal extract-enriched diets to control Aeromonas hydrophila infection in carp

Abstract: This study reports the effect of probiotic-and triherbal extract-enriched diet on Cyprinus carpio (52 ± 2 g, n = 250) inoculated intramuscularly (50 µl) with Aeromonas hydrophila (1.8 × 10 6 CFU ml -1). On Day 6 post-infection, the fish were divided into 4 groups and fed with the basal diet (IU) or with diets supplemented with triherbal extract (H), Sporolac (S) or Lactobacillus (L). A fifth group of non-infected fish fed with the basal diet was used as a control. Haematology and immunology parameters were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 57 publications
(58 reference statements)
2
13
0
Order By: Relevance
“…The present finding is in agreement with some of the earlier studies in olive flounder fed with diets containing an ethyl acetate extract of Punica granatum [17] or E. alba extracts [45,46]. Triherbal extract increased the survival rate in goldfish against Aeromonas hydrophila [18]. Hence, it can be concluded that the enhanced protection observed in the present study is due to the immunostimulatory property of S. glabrescens extract.…”
Section: Discussionsupporting
confidence: 95%
“…The present finding is in agreement with some of the earlier studies in olive flounder fed with diets containing an ethyl acetate extract of Punica granatum [17] or E. alba extracts [45,46]. Triherbal extract increased the survival rate in goldfish against Aeromonas hydrophila [18]. Hence, it can be concluded that the enhanced protection observed in the present study is due to the immunostimulatory property of S. glabrescens extract.…”
Section: Discussionsupporting
confidence: 95%
“…2003). In another experiment, C. carpio fed a triherbal extract‐enriched diet after intramuscular inoculation with A. hydrophila showed a significant increase ( P < 0.05) in respiratory burst activity in weeks 1–4 and comparatively lower mortalities than the control fish (Harikrishnan et al. 2010c).…”
Section: Differential Uses Of Phytochemicals In Finfish Culturementioning
confidence: 97%
“…Different strategies have been used for the oral administration of plants and plant‐derived products in fish (Tables and ). Very frequently plant extracts/plant parts have been included as ingredients of the diet (pellet/extruded feed) at doses ranging from 0.1 to 2% and fish were fed for a period ranging from 2 to 5 weeks, according to a dietary regime (% BW day −1 ) calibrated for fish species and size (Dügenci, Arda & Candan ; Vasudeva, Romesh, Singh & Chakrabarti ; Vasudeva & Chakrabarti , ,b; Vasudeva, Das, Jyotyrmayee & Chakrabarti ; Christybapita, Divyagnaneswari & Michael ; Choi, Park, Yoon, Kim, Jang & Choe ; Awad & Austin ; Harikrishnan, Balasundaram & Heo ; Kirubakaran, Alexander & Michael ; Rattanachaikunsopon & Phumkhachorn ,c; Awad, Mitchell & &Austin Harikrishnan, Kim, Kim, Balasundaram & Heo ,f,g). In other experiments similar percentages of herbs have been included in the diet but fish were fed until satiation or for a longer time period (6–12 weeks) (Kim, Hwang & Bai ; Jian & Wu , ; Shalaby, Khattab & Abdel Rahman ; Yin, Jeney, Racz, Xu, Jun & Jeney ; Ji, Takaoka, Jeong, Lee, Ishimaru, Seoka & Takii ; Ji, Jeong et al .…”
Section: Route Of Plant Administration and Dosagementioning
confidence: 99%
“…) and common carp (Harikrishnan et al . ), being able to induce gradual reduction in the clinical signs, complete recovery of health status and increased survival (Tables and ). Similar results were described by Rajendiran et al .…”
Section: Effects On Fish Resistance To Infectionsmentioning
confidence: 99%